1997
DOI: 10.2527/1997.7551266x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amino acid uptake by the mammary gland of the lactating sow.

Abstract: The objectives of this study were to measure arteriovenous concentration (A-V) differences and estimate uptake of amino acids across the mammary gland in lactating sows. Four sows were used in Trial 1 and nine sows in Trial 2. Cannulas were fitted in the right anterior mammary vein and the carotid artery around d 7 of lactation. Arteriovenous samples were obtained on d 11, 14, 17, and 20. Litters were separated from the sows for 90 min, after which the first blood samples were drawn. Samples were taken at 20-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
4
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 20 publications
7
100
4
2
Order By: Relevance
“…The output of proline in the milk of goats [255], sheep [256], cows [257] and pigs [258] greatly exceeds the uptake of proline by the lactating mammary gland, whereas the uptake of plasma arginine by lactating mammary glands greatly exceeds the output of arginine in the milk [255][256][257][258][259]. Studies with lactating mammary tissues have demonstrated arginine-dependent production of proline [249,257], but there was little or no synthesis of proline from glutamate [249] because of the absence of P5C synthetase [47,249].…”
Section: Arginase and Proline Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The output of proline in the milk of goats [255], sheep [256], cows [257] and pigs [258] greatly exceeds the uptake of proline by the lactating mammary gland, whereas the uptake of plasma arginine by lactating mammary glands greatly exceeds the output of arginine in the milk [255][256][257][258][259]. Studies with lactating mammary tissues have demonstrated arginine-dependent production of proline [249,257], but there was little or no synthesis of proline from glutamate [249] because of the absence of P5C synthetase [47,249].…”
Section: Arginase and Proline Synthesismentioning
confidence: 99%
“…As the high content of these amino acids in milk greatly exceeds their accumulation via uptake by the lactating mammary gland [258,265], they must be synthesized within this organ. As in the case of proline synthesis during lactation, arginase also plays an important role in providing substrate for glutamate synthesis in the mammary gland via type II arginase, OAT and P5C dehydrogenase [249,257].…”
Section: Arginase and Glutamate Synthesismentioning
confidence: 99%
“…TROTTIeR et al (1997) observed that the level of arginine in sow's milk is smaller than the supply of this amino acid to the mammary gland due to its continue degradation by mammary tissue (O'QUINN et al, 2002). In the present study, crude protein or amino acid content of milk, including arginine itself, were not altered by topdressing L-arginine HCL at 1% supplementation, indicating that despite increasing arginine supply in the bloodstream, level of supplementation was not enough to exceed the threshold of arginine degradation in the mammary tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine stimulates the secretion of prolactin and growth hormone (ReYeS et al, 1994) and participates in angiogenesis in mammary tissue (MATeO et al, 2008). Due to the effects of arginine on nitric oxide production and vasodilation, this amino acid causes an increase in local blood flow, resulting in higher nutrient supply which could increase milk production (TROTTIeR et al, 1997;WU & MeININGeR, 2000). Furthermore, the possibility of changing the content of arginine in colostrum and milk could reduce the deficit of this amino acid in newborn piglets (WU et al, 2004;KIM et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3. The dependence of arteriovenous concentration difference (ca -cv) of ten individual free amino acids in goat's mammary gland on their arterial concentration (ca) for control (+H, infusion of balanced mixture) and experimental (-H, infusion of mixture without histidine) periods (calculated from the data of Bequette et al, 2000) A similar dependence was revealed for mammary glands of sows by defining one regression line of arteriovenous difference for 10 individual amino acids on their arterial concentration using mean values from several measurements (Trottier et al, 1997). The authors pointed out also the absence of any relationship between efficiency of extraction and arterial concentration on combined regression for these amino acids, which is predicted by equation (5).…”
Section: Tc a T + Qmentioning
confidence: 99%